(untitled) (Advancements in Homeopathic Research, 2024)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is currently the most researched neurodevelopment disorder in childhood, with poor evidence of confirmatory remedies. Due to its vast diversity in etiological factors, complexity in its psychopathology, most system of medicine fails to provide a long term benefits. The holistic and individualistic principle of Homoeopathy displays a vital role treating such condition effectively without any drug effects or dependence.